Körfez savaşı sonrası Irak'la Türkmenlerin Türkiye'ye göçü ve entegrasyonu - Kürekçi, Birol (My University, 2009)
Türkmenler Kuzey Irak’ta yüzyıllardır yaşayan bir millettir. Irak’taki baskıcı rejimler, istikrarsızlık, etnik çatışma, dış müdahale, savaş gibi sebeplerden Irak Türkmenlerinin bir kısmı muhtelif zamanlarda Türkiye’ye göç etmek zorunda kalmışlardır. Türkiye’ye göç eden Türkmenlerin Türkiye’deki sosyal hayata ne derece uyum sağladıkları merak edilen bir konudur. Bu çalışmamızda Irak Türkmenlerinin tarihi, yaşadıkları olaylar, Körfez Savaşından sonra Türkiye’ye göç etme sebepleri ve Türkiye’deki toplumsal hayata entegrasyonu araştırılmıştır. Türkmen dernekleri ile görüşülerek anket çalışması yapılmış ve Türkmenlerin sosyo-ekonomik durumları istatistiksel analizlerle ortaya konmuştur. Irak Türkmenleri, Sosyal Hayat, Entegrasyon, Türkiye.

Turkmens have been living in Northern Iraq for centuries. Some of these people had to migrate to Turkey in various periods of time due to repressive regimes, instability, ethnic conflicts, foreign intervention and wars in Iraq. The extent of their adaptation to Turkish social life is a matter of interest. In this study, the history of Iraqi Turkmens, the events they have gone through, their reasons of migrating to Turkey after the first Gulf war and their integration to Turkish social life have been analyzed. A survey has been conducted with the cooperation of Turkmens associations and the current situation of Turkmens has been illustrated by means of statistical analysis. Key Words: Migration, Iraqi Turkmens, Social Life, Integration, Turkey.
Keywords: Göçler; Savaşlar_Irak; Tarih; Türkmenler